The “7 Wonders of the World-APP” Augmented Reality-based Media to Improve Elementary School Students’ Conceptual Understanding - Ahmad Ipmawan Kharisma; A.F. Suryaning Ati MZ; Eko Handoyo; Wiwid Widiyanti (Universitas Pendidikan Ganesha, 2023)
Elementary school students cannot visualize virtual objects or images on some social studies materials in a real environment. This study aims to develop 7 Wonders of the World-APP-based Augmented Reality media to improve elementary school student's mastery of concepts. This study used the four-D method and used a pretest-posttest control group design. Methods of data collection using questionnaires and tests. Validity includes the validity of teaching materials, design validity, and learning media validity from two experts. Data analysis techniques using descriptive qualitative analysis, quantitative, and inferential statistics. The results showed that the proportions of the validity test of learning materials, the validity test of the learning media design, and the validity test of the learning media got a very good category. The results of the t-test show significant differences in students' mastery of concepts. Media 7 Wonders of the World-APP, based on Augmented Reality, is very suitable and effective for learning media in elementary schools for social studies.